The Deaths Related to Firearm Injuries During the Age of Childhood in Konya - Demirci, Şerafettin; Doğan, Kamil Hakan; Deniz, İdris; Büken, Bora; Erkol, Zehra Zerrin (The Bulletin of Legal Medicine, 2009)
In this study, it was aimed to examine the deaths related to the firearm injuries during childhood in Konya and the information such as demographic aspects of the cases, the types of the firearms, origin, and the region of injury, place of case, place of death, shooting distance, and the owner of the firearm. With this purpose, the cases which were autopsied by Konya Branch of Forensic Medicine Council and by forensic medicine expert in the districts of Konya between 1999 and 2007 were retrospectively examined. Among 985 death cases at the age of 18 and under; 50 (5.1%) were determined to occur as a result of firearm injuries. The ages of the cases changed between 1 and 18 and the average age was 14.6 + 3.9 (median: 16). 34 cases (68%) were boys while 16 (32%) of them were girls. The rate of boys to girls was 2.1:1. The origin was suicide in 20 cases (40%), accident in 17 cases (34%) and 13 cases (26%) was murder. Shotguns were used in 33 cases (66%) and handguns were use in 17 cases (34%). Only head was injured in 27 cases (54%) while only abdominal region was injured in 10 cases (20%). 29 (70%) of firearm injuries took place at home. 35 cases (70%) died at crime scene and 3 of them (6%) died on the way to hospital. In 24 cases (48%) the shooting was performed adjacently or from a close distant, the shooting were performed from nearby in 11 cases (22%) while 15 shooting cases (30%) were performed from a long distance. In 24 (48%) cases, the gun belonged to the victim’s father. As a result, it was seen that keeping the firearms at homes in the increasing rates would end up with deaths during the childhood age. We think it is necessary and useful for people to avoid from keeping firearms at home or other living quarters, keep them in higher places or under strong locking when they have to since they could lead to suicide or accident originated injuries or deaths if the children easily access to the firearms.Key words: Child, firearm, death, forensic medicine
Keywords: child; firearm; death; forensic medicine